Analisis makna denotatif dan konotatif dalam puisi aḥinnu ilā khubzi ummī karya mahmoud darwish - Irfanudin, Ahmad (Maliki Interdisciplinary Journal, 2025)
This study aims to reveal the types of denotative and connotative meanings in the poem Aḥinnu ilā Khubzi Ummī by Mahmoud Darwish through the approach of ilmu dalalah (semantics). This poem is not only full of expressions of longing, but also becomes a symbolic representation of identity, homeland, and the figure of a mother that is full of emotional and ideological meaning. This study uses a qualitative descriptive method with semantic analysis techniques on the lines of the poem. The results of the study show that the denotative meaning in this poem is seen in the use of everyday diction such as "bread" and "coffee", while the connotative meaning is reflected in the symbolization of the mother as a metaphor for the homeland and irreplaceable love. This study emphasizes the power of poetic language in conveying deep and emotional meanings through the choice of simple but meaningful diction.